PELLETS DE BIOMASSA RESIDUAL DA COLHEITA DE PINUS E EUCALIPTO - Lúcio, Danielle de Moraes (2020)
The energy potential of forest harvest residues allows them to be used as a source of raw material for the production of pellets, as they are low-cost, from sustainable sources and are available all year round. However, its composition, which includes different compartments of the tree, and the time that can be stored in the field are factors that can affect the quality of the pellets produced. This study was based on the thesis that the residual material from the forest harvest can be used in the production of pellets, the objectives being to evaluate the influence of the species, the tree compartments and the storage time on its quality. The pellets were produced in a flat die laboratory pelletizing press using the three compartments (tip, branches and needles/leaves) of pine and eucalyptus, pure and in different mixtures, and using the mixture of biomass obtained from the harvest of pine and eucalyptus in four different storage times in the field. The evaluation of the pellets was carried out by analyzing the physicalmechanical and energetic properties: moisture content, bulk density, unit density, mechanical durability, fines content, proximate analysis, gross calorific value and net calorific value. The quality of the pellets has been compared to ISO 17225-2. Still, for pellets produced with harvest biomass, thermogravimetric analysis was performed. Pinus needles and eucalyptus leaves biomasses contributed to increase the mechanical durability and increase the net and gross calorific value of the pellets, but increased the ash content when mixed with a tip and branches. The pellets of branches, tip and the mixture between these two compartments of pine and eucalyptus showed the lowest values for ash content. Up to 180 days, maximum storage time for residual biomass in the evaluated field, there was no influence on the physical, mechanical and energetic properties of the pellets. Due to their properties, pellets of residual biomass from the pine and eucalyptus harvest can be indicated for industrial use.